Modular Robotics Configurator: A MATLAB Model-Based Development Approach - Ernest Andrei Grosz; Marian Borzan (Applied System Innovation)
In recent years, modularity has become increasingly present in the field of robotics and mechatronics. The need to easily calculate and generate modular robots in an easier and faster way and for a wide range of robotics projects has increased. This paper aims to present a new modular software development method for an automatic configurator of serial robots through the model-based development technique using the MATLAB Simulink R2024b software. Using this functionality, the user has the possibility to configure, generate, and analyze serial robots, starting from a kinematic scheme that complies with the development requirements of the project. Having a high degree of flexibility and avoiding multiple instances of debugging, caused by the need to use different environments, as well as connectivity problems between them or a lack of support in development, the user has the possibility to configure and reconfigure serial robots, easily adapting to the high degree of dynamism in the development of current projects. Because of the modularity on which the software development is based, the user has the possibility to optimize and improve the quality and performance of the system, along with easy adaptation to the speed of technological advancement.